The Influence of Adaptive Organizational Culture, Knowledge Management Capability, and Academic Innovation Climate on Agile Leadership Performance in Higher Education Institutions - Pettalongi, Sagaf S.; Subroto, Desty Endrawati; Suhara, Ade; Nudu, Josef Hernawan; Nawangwulan, Irma M; Anantadjaya, Samuel PD (Yayasan Gema Bina Nusantara, 2025)
Higher education institutions need leaders who can handle the fast-paced changes which currently shape their academic environments. The research investigates how adaptive organizational culture and knowledge management capacity and academic innovation climate affect agile leadership performance in higher education institutions. The study utilized quantitative research methods which required an explanatory research design to conduct its study. The researchers used purposive sampling to collect data from 140 respondents who worked as leaders and academic staff at higher education institutions. The researchers used multiple linear regression to analyze data after they validated the data and confirmed its reliability and tested classical assumptions. The results show that adaptive organizational culture and knowledge management capability and academic innovation climate together with their individual elements create a major positive effect on agile leadership performance. The study results show that organizations can enhance their agile leadership capabilities through two methods which include strengthening their adaptive organizational culture and using effective knowledge management and establishing a positive academic innovation environment. The study provides theoretical contributions to the existing body of knowledge about educational management and organizational leadership. The study results offer practical guidance to higher education institution managers who need to develop leadership programs that promote adaptive skills and innovative capabilities.